Você está na página 1de 1

QUADRADO DA SOMA DE DOIS TERMOS

Observe: (a + b) = ( a + b) . (a + b)
= a + ab+ ab + b
= a + 2ab + b
Concluso:
(primeiro termo) + 2.(primeiro termo) .
(segundo termo) + (segundo termo)
Exemplos :

QUADRADO DA DIFERENA DE DOIS TERMOS


Observe: (a - b) = ( a - b) . (a - b)
= a - ab- ab + b
= a - 2ab + b
Concluso:
(primeiro termo) - 2.(primeiro termo) .
(segundo termo) + (segundo termo)
Exemplos:

1) (5 + x) = 5 + 2.5.x + x = 25 + 10x + x

1) ( 3 X) = 3 + 2.3.X + X = 9 6x + x

2) (2x + 3y) = (2x) + 2.(2x).(3y) + (3y) = 4x +


12xy + 9y

2) (2x -3y) = (2x) -2.(2x).(3y) + (3y) = 4x 12xy+ 9y

Exerccios
1) Calcule

Exerccios
1) Calcule

a) (3 + x) =
b) (x + 5) =
c) ( x + y) =
d) (x + 2) =
e) ( 3x + 2) =
f) (2x + 1) =
g) ( 5+ 3x) =
h) (2x + y) =
i) (r + 4s) =
j) ( 10x + y) =
l) (3y + 3x) =
m) (-5 + n) =
n) (-3x + 5) =
o) (a + ab) =
p) (2x + xy) =
q) (y + 3) =

a) ( 5 x) =
b) (y 3) =
c) (x y) =
d) ( x 7) =
e) (2x 5) =
f) (6y 4) =
g) (3x 2y) =
h) (2x b) =
i) (5x - 1) =
j) (x - 1) =
l) (9x - 1) =
m) (x - 2) =
n) (2m - 3) =
o) (x 5y) =
p) (1 - mx) =
q) (2 - x) =
r) (-3x 5) =
s) (x - m) =